Biomechanical Evaluation of Semi-rigid Junctional Fixation Using a Novel Cable Anchor System to Prevent Proximal Junctional Failure in Adult Spinal Deformity Surgery. Issue 9 (1st May 2022) - Doodkorte, Remco J.P.; Roth, Alex K.; Jacobs, Eva; Arts, Jacobus J.C.; Willems, Paul C.
Abstract : A novel Cable Anchor was compared with other promising techniques in a biomechanical experiment to assess the potential as semi-rigid junctional fixation technique for adult spinal deformity surgery. The achievement of a gradual range of motion transition zone suggests the Cable Anchor may reduce the incidence of proximal junctional failure. Abstract : Study Design: A porcine cadaveric biomechanical study. Objective: To biomechanically evaluate a novel Cable Anchor System as semi-rigid junctional fixation technique for the prevention of proximal junctional failure after adult spinal deformity surgery and to make a comparison to alternative promising prophylactic techniques. Summary of Background Data: The abrupt change of stiffness at the proximal end of a pedicle screw construct is a major risk factor for the development of proximal junctional failure after adult spinal deformity surgery. A number of techniques that aim to provide a gradual transition zone in range of motion (ROM) at the proximal junction have previously been studied. In this study, the design of a novel Cable Anchor System, which comprises a polyethylene cable for rod fixation, is assessed. Methods: Ten T6–T13 porcine spine segments were subjected to cyclic 4 Nm pure-moment loading. The following conditions were tested: uninstrumented, 3 level pedicle screw fixation (PSF), and PSF with supplementary Cable Anchors applied proximally at 1-level (Anchor1) or 2-levels (Anchor2), transverse process hooks (TPH), and 2-level sublaminar tapes (Tape2). The normalized segmental range of motion in the junctional zone was compared using one-way analysis of variance and linear regression. Results: Statistical comparison at the level proximal to PSF showed significantly lower ROMs for all techniques compared to PSF fixation alone in all movement directions. Linear regression demonstrated a higher linearity for Anchor1 (0.820) and Anchor2 (0.923) in the junctional zone in comparison to PSF (1-level: 0.529 and 2-level: 0.421). This linearity was similar to the compared techniques (TPH and Tape2). Conclusion: The Cable Anchor System presented in this study demonstrated a gradual ROM transition zone at the proximal end of a rigid pedicle screw construct similar to TPH and 2-level sublaminar tape semi-rigid junctional fixation constructs, while providing the benefit of preserving the posterior ligament complex. Level of Evidence: 5